SCIENTIFIC-METHODS ASPECTS OF THE ECONOMIC MECHANISM OF THE AGRICULTURAL PRODUCTION COOPERATIVE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The economic mechanism, which functions the enterprise level, should ensure its dynamic development. Such significance of the mentioned mechanism is caused by, that he determines the degree satisfaction economic interests of participants of economic activity of the enterprise. Working out of scientific-methods aspects of the economic mechanism of enterprise acquires especially relevant for the agricultural production cooperative (further – APC) due to the fact, that: 1) this mechanism is complex and multifaceted because it is based on the unique nature of the cooperation; 2) the dynamics of the number of registered APCs in Ukraine is consistently small, as their numbers amounted to 996 units at beginning of 2018 and decreased by 23,2% in 2011–2018.The purpose of article is to study scientific-methods aspects of the economic mechanism of the APC taking into account the peculiarities of its manifestation at separate stages reproduction of economic activity of this enterprise.The economic mechanism of the APC encompasses the system unity of economic forms, methods and instruments used to regulate relations in this enterprise. This mechanism may have different degrees of perfection, depending on its specific content. At same time, the economic mechanism of the APC has a different content on the stages of production, distribution, exchange and consumption of the results economic activity of this enterprise. The special role in development of the enterprise belongs to the economic mechanism that regulates relations on the stage of distribution. This is due to that the forms, methods and instruments of distribution the final results economic activity of the APC directly determine the degree satisfaction economic interests of members of the cooperative, its associate members and hired workers. The essential components of the economic mechanism of the APC on the stage of distribution of the results of its economic activity are: 1) methods and algorithm for formation indicators that determine the final results of the economic activity of the APC and are subject to further distribution; 2) methods and algorithm for formation of indicators obtained as a result of distribution of final products and income the APC.The objective indicator of the final results of the economic activity of the APC on the initial stage of distribution of these results is the amount of final output of the enterprise for reporting year. The final indicator of distribution the final results economic activities of the APC is income that is generated on a residual basis. This indicator is subject to further distribution between the funds created at the enterprise and participants of its economic activity.
Keywords: economic mechanism, agricultural production cooperative, distribution of final results